A Web Based Fuzzy Expert System for Human Disease Diagnosis (International Journal of Engineering and Computer Science, 2015)
Fuzzy expert system has shown a remarkable tool for building of intelligent decision making systems based on expert’s knowledge and observations. This work presents an approach for the treatment of patients on the basis of fuzzy rules applied on symptoms that seen in patient. For the identification of complex disease like ADHD, SLP and IBS, firstly fuzzy rules applied based on the symptoms selected by the patient and secondly for the improvement of developed system, expert learning system is proposed by which disease diagnosis accuracy has been enhanced. Through exert learning system, experience Doctors around the world can share their knowledge with the system for enhance the probability of finding diseases more accurately. Finally, a tool named “Diagnosis Portal” has to be developed for showing the proposed work and our results shows improved interpretation accuracy in treatment of patient with faster and accurate manner.